2020
DOI: 10.21203/rs.3.rs-29759/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 pandemic and bariatric surgery in Argentina

Abstract: Background: The SARS-CoV2 virus pandemic pandemic has been characterized for its rapid global dispersion. Obesity is an independent risk factor for the most severe cases of COVID -19. The impact in Argentina differs from others since it was able to anticipate public health interventions in order to flatten the contagion curve. Early quarantine achieved better control of the pandemic and, following the recommendations of scientific societies in countries with higher affectation, elective bariatric surgeries (BS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…A J o u r n a l P r e -p r o o f similar survey in the UK found that 97% of bariatric surgeons ceased their outpatient clinics for both new and follow-up patients and almost 60% of bariatric surgeons stopped placing new patients on their waiting lists 29 . In Argentina, a survey found that 99% of bariatric surgeons ceased all their elective bariatric surgeries, with a mean of 7.7 days prior to the first regional case 30 .…”
Section: Healthcare and The Covid-19 Impact On Obesitymentioning
confidence: 99%
“…A J o u r n a l P r e -p r o o f similar survey in the UK found that 97% of bariatric surgeons ceased their outpatient clinics for both new and follow-up patients and almost 60% of bariatric surgeons stopped placing new patients on their waiting lists 29 . In Argentina, a survey found that 99% of bariatric surgeons ceased all their elective bariatric surgeries, with a mean of 7.7 days prior to the first regional case 30 .…”
Section: Healthcare and The Covid-19 Impact On Obesitymentioning
confidence: 99%